Mathematical modelling of wave impacts on seaward-inclined seawall - Mohd Shahridwan, Ramli; Fadhlyya Arawaney, Abdul Ghani; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Greenhow, Martin (IOP Publishing, 2017)
In this study, the numerical investigation of a mathematical model of wave impacts on an inclined seawall is considered, using an extension of Cooker’s model for vertical seawalls due to Greenhow, who considered a perturbation model to study the effect of small wall inclinations from the vertical. Cooker used pressure impulse theory to simplify the highly time-dependent and very nonlinear boundary-value problem (bvp) by considering the time integral of the pressure during the duration of the impact pressure-impulse. The solution to this bvp is found by solving Laplace’s Equation for simplified boundary conditions. The perturbation theory gives a series of bvps which are solved analytically by MATLAB. The relation between the pressure impulse and the inclination angle of a wall is investigated. We find that as the seaward or landward inclination of the seawall increases, the pressure impulse increases.